2012
DOI: 10.1186/1476-511x-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of lipometabolism-related miR-122 and miR-370 are increased in patients with hyperlipidemia and associated with coronary artery disease

Abstract: BackgroundHyperlipidemia plays a crucial role in the development and progression of coronary artery disease (CAD). Recent studies have identified that microRNAs (miRNAs) are important regulators of lipid metabolism, but little is known about the circulating levels of lipometabolism-related miRNAs and their relationship with the presence of CAD in patients with hyperlipidemia.MethodsIn the present study, we enrolled a total of 255 hyperlipidemia patients with or without CAD and 100 controls with normal blood li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(148 citation statements)
references
References 28 publications
13
131
2
2
Order By: Relevance
“…21 MiR-122-5p was found to be overexpressed in the liver of hyperlipidemic animals 22 and increased in the bloodstream of patients with hyperlipidemia, being positively correlated with total cholesterol, triglycerides and low-density lipoprotein cholesterol. 23 In a porcine model of cardiogenic shock, Andersson et al 24 described a significant increase in the circulating levels of miR-122-5p, the magnitude of which was superior to the cardiac-enriched miRNAs. Interestingly, this increase did not seem to be explained by liver ischemia and was attenuated by therapeutic hypothermia.…”
Section: Quantification Of Classical Biomarkersmentioning
confidence: 99%
“…21 MiR-122-5p was found to be overexpressed in the liver of hyperlipidemic animals 22 and increased in the bloodstream of patients with hyperlipidemia, being positively correlated with total cholesterol, triglycerides and low-density lipoprotein cholesterol. 23 In a porcine model of cardiogenic shock, Andersson et al 24 described a significant increase in the circulating levels of miR-122-5p, the magnitude of which was superior to the cardiac-enriched miRNAs. Interestingly, this increase did not seem to be explained by liver ischemia and was attenuated by therapeutic hypothermia.…”
Section: Quantification Of Classical Biomarkersmentioning
confidence: 99%
“…Interestingly both miR-122 and miR-370 correlated positively with levels of total cholesterol, triglyceride, and low-density lipoprotein (LDL)-cholesterol in the plasma of both patient and control cohorts. Of note, miR-122 and miR-370 were both found to be decreased with statin treatment [40], suggesting these miRNAs as both potential diagnostic biomarkers for hyperlipidaemia and predictive biomarkers for response to statins. Table 2, row K) and collected visceral and subcutaneous abdominal adipose tissue biopsies.…”
Section: _ T D $ D I F F ] Refsmentioning
confidence: 98%
“…However, circulating levels of miR-370 and miR-122 have been reported for individuals with hyperlipidaemia, a risk factor for MetS [39]. Gao et al [40] reported that in a cohort of 255 hyperlipidaemia individuals presenting with or without CAD in comparison with 100 healthy controls ( Table 2, row J), plasma levels of four lipid metabolism-associated miRNAs (miR-122, miR-370, miR-33a, and miR-33b) were investigated. Here, miR-122 and miR-370 were both found to be significantly increased in the plasma of hyperlipidaemia individuals compared with that of healthy controls, while miR-33a and miR-33b were undetected.…”
Section: _ T D $ D I F F ] Refsmentioning
confidence: 99%
“…Particularly increased level of miR-423-5p was well correlated with heart failure in different studies [53] [57]. Similarly level of miR-122 and miR-370 were positively correlated with total cholesterol, Triglycerides and LDL cholesterol (LDL C) and coronary artery disease (CAD) progression [71].…”
Section: Circulating Mirna As a Diagnostic Indicator Of Cardiovasculamentioning
confidence: 89%
“…Similarly anti miR-33 therapy has found to be atheroprotective by increasing circulating HDL in mice model [70]. A study done by Gao et al [71] in 355 Chinese patients with hyperlipidemia found that level of miR-122 and miR-370 were positively correlated with total cholesterol, Triglycerides and Low density lipoprotein cholesterol C (LDL-C) and coronary artery disease (CAD) progression.…”
Section: Atherosclerosismentioning
confidence: 99%